Emergency contraceptive pill usage: how community pharmacists can communicate with young female adults? - Leiu, Chang You; Omar, Zoharah; Alias, Siti Noormi; Abd Rahim, Nur Aira (Human Resource Management Academic Research Society, 2020)
Emergency contraceptive pill (ECP) have been widely used by young women across the world to prevent unwanted pregnancy after an unprotected sexual intercourse. Community pharmacists are first line healthcare providers and play pivotal role in communicating correct use of emergency contraceptive pill. Given that the study of a communication guide particularly in the Malaysian setting is limited, this paper aims to explore the current pharmacy practice and effective communication channels in supply of emergency contraceptive pill to young female adults. Underpinning theory of Extended Parallel Process Model (EPPM) and Theory-informed media selection (TIMS) framework is discussed in the design of a health communication material. The outcome of study implies pharmacists to form an effective ECP communication channels to their respective pharmacy settings and to inform policy makers in the exploration of novel ECP information distribution channels in various healthcare settings in providing ECP information.